Anaplastic large cell lymphoma ALK-negative clinically mimicking alcoholic hepatitis - a review - Fernando Peixoto Ferraz de Campos; Aloísio Felipe-Silva; Maria Claudia Nogueira Zerbini (University of São Paulo, 2013)
Anaplastic large cell lymphoma (ALCL), described less than 30 years ago by Karl Lennert and Herald Stein in Kiel, West Germany, is a T-cell or null non-Hodgkin lymphoma, with distinctive morphology (hallmark cells, prominent sinus and/or perivascular growth pattern), characteristic immunophenotype (CD30+, cytotoxic granules protein+, CD3-/+) and specific genetic features as translocations involving the receptor tyrosine kinase called anaplastic lymphoma kinase (ALK) on 2p23 and variable partners genes, which results in the expression of ALK fusion protein. The absence of ALK expression is also observed and is associated with poorer prognosis that seen with ALK expression. ALK-negative ALCL is more frequent in adults, with both nodal and extra nodal clinical presentation and includes several differential diagnoses with other CD30+ lymphomas. Liver involvement by ALCL is rare and is generally seen as mass formation; the diffuse pattern of infiltration is even more unusual. The authors present a case of a 72-year-old man who presented clinical symptoms of acute hepatic failure. The patient had a long history of alcohol abuse and the diagnosis of alcoholic hepatitis was highly considered, although the serum lactic dehydrogenase (LDH) value was highly elevated. The clinical course was fulminant leading to death on the fourth day of hospitalization. Autopsy demonstrated diffuse neoplastic hepatic infiltration as well as splenic, pulmonary, bone marrow, and minor abdominal lymph nodes involvement by the tumor. Based on morphological, immunophenotypical, and immunohistochemical features, a diagnosis of ALK- negative ALCL was concluded. When there is marked elevation of LDH the possibility of lymphoma, ALCL and other types, should be the principal diagnosis to be considered.